2018
DOI: 10.1111/eth.12764
|View full text |Cite
|
Sign up to set email alerts
|

Ravens adjust their antipredatory responses to con‐ and hetero‐specific alarms to the perceived threat

Abstract: Heterospecific alarm calls are typically found in situations where multiple species have a common predator. In birds, they are particularly common in mixed mixed‐species flocks. In species with highly developed social and cognitive abilities like corvids, there is the potential for differential responses to heterospecific vs. conspecific calls according to the riskiness of the habitat. We tested the responses of free‐ranging ravens (Corvus corax) to conspecific alarm calls and compared them to heterospecific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For data collection, we chose the enclosure of wild boars Sus scrofa as the enclosure's landscape allowed an excellent view of the feeding site and its surroundings. Furthermore, compared to the feedings of large predators like wolves Canis lupus and bears Ursos arctos , wild boars do not show any aggressive food defence towards ravens (Bugnyar & Kotrschal, ; Nácarová, Veselý, & Bugnyar, ).…”
Section: Methodsmentioning
confidence: 99%
“…For data collection, we chose the enclosure of wild boars Sus scrofa as the enclosure's landscape allowed an excellent view of the feeding site and its surroundings. Furthermore, compared to the feedings of large predators like wolves Canis lupus and bears Ursos arctos , wild boars do not show any aggressive food defence towards ravens (Bugnyar & Kotrschal, ; Nácarová, Veselý, & Bugnyar, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although ravens face severe foraging competition in winter (Heinrich, 1989) and may divide their attention between gaining access to food (B. Heinrich & Marzluff, 1995), fending off conspecific kleptoparasitism and cache pilferage (Bugnyar & Kotrschal, 2002;Gallego-Abenza, Loretto, & Bugnyar, 2020;Heinrich & Pepper, 1998), there are hardly any indications that competition for food affects their antipredator behaviour, at least not at our study site (Nácarová et al, 2018). Finally, the temporal pattern found might be considered an artefact of our testing.…”
Section: Discussionmentioning
confidence: 80%
“…Such assessment capability by receivers was also documented in small mammals, precisely in adult Richardson´s ground squirrels (Sloan & Hare, 2008). When confronted with alarm calls from conspecifics and closely related heterospecifics during foraging, carrion crows tended to respond to any alarm calls (Bílá, Beránková, Veselý, Bugnyar, & Schwab, 2017), whereas ravens adjusted their antipredator behaviour depending on the perceived risk (whether or not they snatched food from predators; Nácarová, Veselý, & Bugnyar, 2018) and the familiarity of the calling species (Davidkova, Veselý, Syrova, Nacarovà, & Bugnyar, 2020).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Frid and Dill (2002) suggested that "disturbance stimuli should be analogous to predation risk" and list vigilance as a response to disturbance. These disturbance stimuli include vocalizations of other species, as eavesdropping on heterospecific vocalizations allows individuals to detect the presence of a predator (Magrath et al, 2015).Common ravens (Corvus corax), for instance, respond to playback of jackdaw (Corvus monedula), blue jay (Cyanocitta cristata), European jay (Garrulus glandarius), and laughing gull (Leucophaeus atricilla) alarm calls with flight or vigilance (Davídková et al, 2020;Nácarová et al, 2018).…”
Section: Eavesdropping On Speechmentioning
confidence: 99%